(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Sustainable tourism is an approach and method upon which many international tourism institutions are based, it is one of the most important concepts and types of the tourism industry that emerged in the 1970s and since environmental protection is a major issue in recent years due to the importance of environmental awareness. Local development without affecting the environment, society and the economy, the application of the concept of sustainable tourism relates to three aspects, which are the material return for the owners of tourism projects, the social dimension and the environmental dimension, as tourism institutions are part of the environment that must preserve their natural resources and the dimension that any negative impact harms the environment. The study problem was identified on how to achieve the tourism environmental sustainability of the residential units of Al-Uqair Beach in Al-Ahsa, Saudi Arabia. The study aims to shed light on the importance of sustainable tourism and how to achieve it in the Kingdom of Saudi Arabia, which is one of the main objectives of the Kingdom’s Vision 2030, in order to reduce the damage caused by Traditional methods in architecture and interior architecture, taking into account the environmental terms in construction and planning according to tourism plans that apply the principles of sustainable development. The researcher used the descriptive, analytical and experimental approach by study the proposed sustainable interior designs for the tourist housing units in Al-Uqair Beach in Al-Ahsa, Saudi Arabia. The study defines the role and importance of the sustainable interior design of the design-proposed tourist housing units at Al-Uqair Beach in enhancing the quality of the internal environment towards a tourism environmental sustainability and how to choose materials, starting from the selection of building materials for residential units and ending with sustainable interior designs, that achieve the requirements of tourism development and environmental protection. And reach the least possible negative impact on the environment. This leads to energy efficiency, avoiding environmental toxins, and using materials and resources in a responsible manner with a positive physical and psychological impact on the occupants of these tourist housing units.